(untitled) (International Journal of Engineering Management Science, 2024)
A DC motor is essential for a variety of industrial applications. This project uses the Internet of Things to monitor and control a number of characteristics, including temperature, speed, and other variables, in addition to protecting the DC motor (IoT). NodeMCU-ESP8266 WiFi modules, a DC motor, an NTC thermocouple temperature sensor, a relay, and other components are used in this project. We use the Internet of Things (IoT) for process monitoring and control, which enables us to store real-time values on a web server and control multiple activities from a great distance. Here, a user interface will be used to control the entire system (pc or smartphone). The IoT cloud interface can be used to send and receive signals with the assistance of the Wi-Fi module ESP8266 (NodeMCU). This system is made to operate a DC motor without stopping the entire operation, or work stoppage. It aids in system monitoring and, in the event that the temperature rises, lowers it without endangering the system by counterclockwise rotating a DC motor.